Streptomyces tyrfis sp. nov., an actinobacterium isolated from Thai peat swamp forest soil and its promising secondary metabolites - Penkawee Kottip; Khanungkan Klanbut; Poowadon Fukasem; Pattama Pittayakhajonwut; Chakapong Intaraudom; Nantiya Bunbamrung; Chanwit Suriyachadkun; Montri Yasawong; Ya‐Wen He; Somboon Tanasupawat; Sarin Tadtong; Chitti Thawai (Scientific Reports, 2026)
An actinomycete strain, PTD5-9T, was isolated from peat swamp forest soil in Narathiwat Province, Thailand. Chemotaxonomic features and phylogenetic analysis based on the 16S rRNA gene sequence placed this strain within the genus Streptomyces. It exhibited the highest sequence similarity to Streptomyces gelaticus NRRL B-2928ᵀ (99.38%) and Streptomyces sanglieri NBRC 100784ᵀ (99.31%). However, the average nucleotide identity based on MUMmer (ANIm) values (88.48–88.56%), the average amino acid identity (84.37–84.97%), and digital DNA–DNA hybridization (dDDH) estimates (31.2–36.5%) were significantly below the accepted thresholds for species demarcation, supporting its classification as a new species within the genus. Accordingly, the name Streptomyces tyrfis sp. nov. is proposed. The crude extract derived from the culture broth of strain PTD5-9ᵀ exhibited potent antibacterial activity against Gram-positive bacteria (MIC ≤ 250 µg/mL). Subsequent chemical analysis led to the identification of ten bioactive secondary metabolites: isocycloheximide (1), (2R,4S,6E)-anhydrocycloheximide (2), actiphenol (3), (−)-phenatic acid A (4), 8-O-methyltetrangomycin (5), 8-O-methylrabelomycin (6), 4-hydroxy-8-O-methylrabelomycin (7), tetrangulol methyl ether (also known as X-14881 E) (8), (−)-elmonin (9), and 2-phenylacetamide (10). Among these, compounds 3, 6, 7, and 8, which were isolated in sufficient quantities, exhibited notable inhibitory activity against Mycobacterium tuberculosis, with MIC values ranging from 3.13 to 25.0 µg/mL. Furthermore, compounds 6, 7, and 8 demonstrated pronounced cytotoxicity against human small cell lung cancer (NCI-H187) cells (IC₅₀: 1.10–7.80 µM), and against human breast cancer (MCF-7) cells (IC₅₀: 1.21–24.6 µM).
Keywords: Microbial Natural Products and Biosynthesis; Genomics and Phylogenetic Studies; Advanced Synthetic Organic Chemistry